Preface of Mini Symposia of 82-Statistical Methods and Applications in Engineering - Greenacre, Zerrin Aşan; Atay, Mehmet Tarık; Gazeloǧlu, Cengiz (American Institute of Physics Inc., 2018)
Preface of Mini Symposia of 82-Statistical Methods and Applications in Engineering